Effects of incubation and polyphenol oxidase enrichment on colour, fermentation index, procyanidins and astringency of unfermented and partly fermented cocoa beans - Misnawi; Jinap, S.; Jamilah, B.; Nazamid, S. (Blackwell Publishing, 2003)
Incubation of unfermented and partly fermented cocoa beans in acetate buffer, pH 5.5, at 45 °C increased yellowness, total colour differences and fermentation index value of the cocoa bean powders and decreased cocoa procyanidins (monomers to pentamers), and their astringency. Fermentation index and (-)-epicatechin content, equivalent to those of fully fermented beans, were reached by unfermented beans after 4-8-h incubation, but not by partly fermented beans even after 16 h. During incubation of partly fermented cocoa beans enriched with polyphenol oxidase, yellowness and fermentation index value were increased, whilst (-)-epicatechin was decreased. Tyrosinase had a less significant effect in yellow colour formation, but showed a significant reduction of (-)-epicatechin and increase in fermentation index compared with crude cocoa polyphenol oxidase. However, both enzymes have similar effects on procyanidin degradation and astringent taste reduction. Incubation of cocoa beans for 16 h increased the cut test score of unfermented and partly fermented beans by 50 and 30%, respectively.